The Effect of Argument-Driven Inquiry (ADI) Model on Students' Critical Thinking Skills in Writing Argumentation Texts - Lia Desi Amelia; Khaerudin Kurniawan; Isah Cahyani (Universitas Muhammadiyah Malang, 2025)
Critical thinking is an essential 21st-century skill that must be developed in Indonesian language learning, especially in writing argumentative texts. However, students' critical thinking skills remain low due to learning approaches that do not sufficiently encourage idea exploration and the structured development of arguments. This study aims to determine the effectiveness of the Argument-Driven Inquiry (ADI) learning model in improving high school students' critical thinking skills in writing argumentative texts. The research employed a quantitative approach with a quasi-experimental method. The sample consisted of two classes: the experimental class, which was taught using the ADI model, and the control class, which received conventional instruction. Data were collected using a critical thinking skills test administered before and after the treatment. Assumption tests, including normality and homogeneity, were conducted before the independent t-test was used for data analysis. The results showed that the experimental group experienced an average posttest score increase of 11.14 points, and the t-test yielded a significance value of 0.000 < 0.05, indicating a statistically significant difference between the two groups. The Argument-Driven Inquiry (ADI) model effectively enhances students' critical thinking skills in writing argumentative texts and offers a relevant alternative to improve the quality of Indonesian language learning.